KEBIJAKAN AUSTRALIA DALAM PENANGANAN PENCARI SUAKA MELALUI OPERATION SOVEREIGN BORDERS ERA TONY ABBOTT (TAHUN 2013 -2015) - Arsha Rahmadhani (2020)
This study departs from the contradiction of Australia's commitment as a ratifying country to the 1951 Refugee Status Related Convention with the asylum seeker policy under Tony Abbott's administration, namely Operation Sovereign Borders. In 2013, the liberal coalition government of Australia under the leadership of Prime Minister Tony Abbott announced it would impose a turn back the boats policy as a key element of Operation Sovereign Borders policy. Operation Sovereign Borders, which came into force on 18 September 2013, is actually a military operation with a securitization approach to prevent and restore asylum seekers seeking access to asylum in Australia. This research then attempts to analyze the securitization efforts made by the Abbott government, in the process, the securitization undertaken by the Abbott government involves the mass media to form opinions and gain public support. In analyzing, the author uses qualitative methods with the theory of securitization, sovereignty, and the concept of illegal migration. The results of this study indicate the existence of framing and politicization of the phenomenon of asylum seekers as a threat to Australia's sovereignty, so that in handling this it requires an extraordinary policy which is the legitimacy of the use of the military against asylum seekers. Keywords: Asylum Seekers, Australia, Operation Sovereign Borders, Securitization, Illegal Migration